Greening India's Growth : Costs, Valuations and Trade-offs - Mani, Muthukumara S. (New York: Routledge, 2015)
India’s sustained and rapid economic growth offers an opportunity to lift millions out of poverty. But this may come at a steep cost to the nation’s environment and natural resources. This insightful book analyzes India’s growth from an economic perspective and assesses whether India can grow in a “green” and sustainable manner. Three key issues are addressed. The first is the physical and monetary costs and losses of environmental health and natural resources driven by economic growth. The authors undertake a monetary valuation and quantification of environmental damage, using techniques that have been developed to better understand and quantify preferences and values of individuals and communities in the context of environmental quality, conservation of natural resources, and environmental health risks. The second part estimates the value of ecosystem services from the major biomes in India using state-of-the art methods with a view to preserving them for the future. The third section provides a menu of policy instruments to explore trade-offs between economic growth and environmental sustainability using a computable general equilibrium approach with particular attention to air pollution. The conclusions focus on the way forward in terms of policies, measures, and instruments as India seeks to balance the twin challenges of maintaining economic prosperity and simultaneously managing its environmental resources. This original version is also available at www.Routledge.com/9780415719353.